Solid‐phase synthesis of three‐armed star‐shaped peptoids and their hierarchical self‐assembly. Issue 4 (24th January 2019) - Jin, Haibao; Jian, Tengyue; Ding, Yan‐Huai; Chen, Yulin; Mu, Peng; Wang, Lei; Chen, Chun‐Long
Abstract : Due to the branched structure feature and unique properties, a variety of star‐shaped polymers have been designed and synthesized. Despite those advances, solid‐phase synthesis of star‐shaped sequence‐defined synthetic polymers that exhibit hierarchical self‐assembly remains a significant challenge. Hence, we present an effective strategy for the solid‐phase synthesis of three‐armed star‐shaped peptoids, in which ethylenediamine was used as the centric star pivot. Based on the sequence of monomer addition, a series of AA′A′′‐type and ABB′‐type peptoids were synthesized and characterized by UPLC‐MS (ultrahigh performance liquid chromatography‐mass spectrometry). By taking advantage of the easy‐synthesis and large side‐chain diversity, we synthesized star‐shaped peptoids with tunable functions. We further demonstrated the aqueous self‐assembly of some representative peptoids into biomimetic nanomaterials with well‐defined hierarchical structures, such as nanofibers and nanotubes. These results indicate that star‐shaped peptoids offer the potential in self‐assembly of biomimetic nanomaterials with tunable chemistries and functions. Abstract :